Transplantation of autologous bone marrow-derived mesenchymal stem cells under arthroscopic surgery with microfracture versus microfracture alone for articular cartilage lesions in the knee: A multicenter prospective randomized control clinical trial - Hashimoto, Yusuke; Nishida, Yohei; Takahashi, Shinji; Nakamura, Hiroaki; Mera, Hisashi; Kashiwa, Kaori; Yoshiya, Shinichi; Inagaki, Yusuke; Uematsu, Kota; Tanaka, Yasuhito; Asada, Shigeki; Akagi, Masao; et al. (Regenerative therapy, 2019)
To investigate the efficacy of the transplantation of autologous bone marrow-derived mesenchymal stem cells (BMSCs) under arthroscopy with microfracture (MFX) compared with microfracture alone. Eleven patients with a symptomatic articular cartilage defect of the knee were included in the study. They were randomized to receive BMSCs with MFX (cell-T group, n=7) or MFX alone (control group, n=4). Clinical results were evaluated using International Knee Documentation committee (IKDC) knee evaluation questionnaires and the Knee Injury and Osteoarthritis Outcome Score (KOOS) before and 48 weeks after surgery. Quantitative and qualitative assessments of repair tissue were carried out at 48 weeks by T2 mapping of magnetic resonance images (MRIs) and the magnetic resonance observation of cartilage repair tissue (MOCART) scoring system with follow-up MRI. No significant differences between preoperative and postoperative IKDC and KOOS were observed in the cell-T or control group. However, forty-eight weeks after surgery, the cell-T group showed a trend for a greater KOOS QOL score compared with the control group (79.4 vs. 39.1, respectively; P=0.07). The T2 value did not differ significantly between the two groups, but the mean MOCART score was significantly higher in the cell-T group than in the control group (P=0.02). Compared with MFX alone, BMSC transplantation with MFX resulted in better postoperative healing of the cartilage and subchondral bone as determined by the MOCART score. Clinically, BMSC transplantation with MFX gave a higher KOOS QOL score after 48 weeks. •This is the first prospective randomized clinical trial between BMSCs with MFX and MFX alone.•BMSCs with MFX showed a trend for a greater KOOS QOL score compared with MFX alone.•BMSCs with MFX resulted in better healing of the cartilage by the MOCART score.